1998
DOI: 10.1001/jama.280.22.1915
|View full text |Cite
|
Sign up to set email alerts
|

Declining Blood Lead Levels and Changes in Cognitive Function During Childhood

Abstract: Context.-Many studies have found a significant inverse association between early exposure to environmental lead and cognitive function in childhood. Whether these effects are reversible when exposure is reduced is not clear. Objective.-To assess the reversibility of the apparent effects of lead on cognitive abilities in early childhood by testing whether declines in blood lead concentrations beyond the age of 2 years are associated with improvements in cognition. Setting.-Urban and rural communities surroundin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
83
0
3

Year Published

1999
1999
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 130 publications
(88 citation statements)
references
References 32 publications
(36 reference statements)
2
83
0
3
Order By: Relevance
“…Those whose blood lead concentrations decreased the most had improved cognitive test scores independent of whether they had been given iron or chelation therapy. 35 An Australian study 36 of 375 children with longer follow-up, however, found only small and inconsistent improvement in the IQs of children whose blood lead concentrations decreased the most. A large (780-children) randomized trial of the use of succimer in children with blood lead concentrations of 20 to 44 g/dL, the Treatment of Lead-Exposed Children (TLC) 3 Trial, showed no benefit on cognitive or neuropsychologic testing despite an abrupt but transient decrease in the treated children's blood lead concentrations.…”
Section: Reversibilitymentioning
confidence: 99%
“…Those whose blood lead concentrations decreased the most had improved cognitive test scores independent of whether they had been given iron or chelation therapy. 35 An Australian study 36 of 375 children with longer follow-up, however, found only small and inconsistent improvement in the IQs of children whose blood lead concentrations decreased the most. A large (780-children) randomized trial of the use of succimer in children with blood lead concentrations of 20 to 44 g/dL, the Treatment of Lead-Exposed Children (TLC) 3 Trial, showed no benefit on cognitive or neuropsychologic testing despite an abrupt but transient decrease in the treated children's blood lead concentrations.…”
Section: Reversibilitymentioning
confidence: 99%
“…At age 7 years, both prenatal and postnatal PbB were inversely associated with visual motor performance (Baghurst et al 1995). Analysis of the relationship between individual changes in PbB and individual changes in measures of cognitive development during the life of the cohort found that the mean PbB in the children decreased from 21.2 μg/dL at age 2 years to 7.9 μg/dL at age 11-13 years; however, cognitive scores in children whose blood lead concentration declined the most were generally not improved relative to the scores of children whose PbB declined least (Tong et al 1998). Changes in IQ and declines in PbB that occurred between the ages of 7 and 11-13 years suggested better cognition among children whose PbB declined most.…”
Section: Health Effectsmentioning
confidence: 99%
“…Death from encephalopathy may occur with PbBs ≥125 μg/dL. In addition to the above effects, the following health effects have been associated with lead exposures either in utero, during infancy, or during childhood: delays or impairment of neurological development, neurobehavioral deficits including IQ deficits, low birth weight, and low gestational age, growth retardation, and delayed sexual maturation in girls (Bellinger et al 1992;Canfield et al 2004;Coscia et al 2003;Lanphear et al 2000a;Ris et al 2004;Schnaas et al 2000;Selevan et al 2003;Tong et al 1998;Wu et al 2003a). These effects, which are discussed in Section 3.2, are consistent with findings in animals exposed to lead.…”
Section: Health Effectsmentioning
confidence: 99%
“…corresponding to the blood lead concentration of less than 25 µg/dL (Tong et al, 1998). In 2006, in Circulation, Menke et al published data from NHANES analysis showing the association between blood lead level and mortality from both myocardial infarction and stroke.…”
Section: The Dependence Of Circulatory System Changes On Body Lead Bumentioning
confidence: 99%